Chameleonism Revisited: Imposters, Hypocrites, and Passing. (4th May 2023) - Sassower, Raphael
ABSTRACT: This paper looks at a constellation of three interrelated figures, the hypocrite, the imposter, and the chameleon, all of whom deceive others and at times themselves as they present themselves and are examined by others in different social settings. On closer examination, different facets of their public presentations come to light, some related to their motives, some to the expected goals of their conduct. The conduct of hypocrites overlaps with and resembles imposters insofar as they both suggest a possible nefarious intentionality associated with undeserved outcomes or gains, as compared with chameleons, who seem at most to camouflage themselves in order to become undetected in their environments. The deceptive (and occasionally self-deceptive) character of the conduct of all three figures (whether understood interchangeably or not) remains of interest beyond the circles of social theorists and political pundits at least in the sense that it is condemnable as much as it is condemning, though to different degrees.